KEMAMPUAN DAN STRATEGI PEMECAHAN MASALAH PADA MATERI BARISAN DAN DERET ARITMATIKA DI SMP - Sari, Roshinta Indah; Yusmin, Edy; Suratman, Dede (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The fact in math education is the student’s problem solving ability that is still low. In solving problem, student just apply one problem solving strategy. Problem solving ability and strategy are influenced by some factors, one of them is student’s learning style. Therefore, problem-solving ability and strategy should be analyzed based on student’s learning styles. The purpose of this research is to determine the problem solving ability and strategy based on learning style in arithmetic sequence and series at SMP 3 Pontianak. Learning styles in this research is learning style that is developed by Kolb that are diverger, assimilator, converger. and accommodator. The research method used is descriptive and the form of research is case study. Subjects in this research are 7 students from all of learning style. The results in this research shows that the problem solving ability varies based on the learning style. Students who have the highest problem solving abilities are students with converger learning style. Students with diverger and accommodator learning styles have problem solving skills with medium category. Students who have the lowest problem solving abilities are students with assimilator learning style. Furthermore, most of all students used open sentence strategy as problem solving strategy. Keywords: Problem-Solving Ability and Strategy, Learning Style